2005
DOI: 10.1556/abiol.56.2005.3-4.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antipyretic drugs on the labeling of blood elements with Technetium-99m

Abstract: Acetaminophen (AAP), acetylsalicylic acid (ASA) and dipyrone (DIP) are antipyretic and analgesics drugs that have wide use in health sciences. Some drugs can modify the labeling of blood elements with technetium-99m (99mTc). This work has evaluated the effect of AAP, ASA and DIP on the labeling of the blood elements with 99mTc. Blood was incubated with different concentrations of the drugs before the 99mTc-labeled process. Plasma (P), blood cells (BC), insoluble (IF-P, IF-BC) and soluble (SF-P, SF-BC) fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…There are evidences that various medicinal plants can affect either radiolabeling or biodistribution of red cells in the context of the nuclear medicine clinic, and a number of workers have turned their attention to in vitro testing of the drug (synthetic/natural) with 99mTC labeled blood cells (Hladik et al, 1982(Hladik et al, , 1987Sampson, 1996;Frydman et al, 2004;Fonseca et al, 2005). Furthermore, the developing of model that permits to evaluate pharmacologic properties of natural products is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are evidences that various medicinal plants can affect either radiolabeling or biodistribution of red cells in the context of the nuclear medicine clinic, and a number of workers have turned their attention to in vitro testing of the drug (synthetic/natural) with 99mTC labeled blood cells (Hladik et al, 1982(Hladik et al, , 1987Sampson, 1996;Frydman et al, 2004;Fonseca et al, 2005). Furthermore, the developing of model that permits to evaluate pharmacologic properties of natural products is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…It is described that natural and synthetic products can alter the labeling of blood constituents with 99mTc (Frydman et al, 2004;Valenca et al, 2005;Fonseca et al, 2005). The labeling of blood constituents could decrease due to the action of drugs (natural and synthetic) in (1) binding at the same sites on the blood constituents, (2) direct inhibition (chelating action) of the stannous (Sn +2 ) and pertechnetate ions (99mTcO -), (3) direct oxidation or generation of free radicals that could oxidize the stannous ion, (4) antioxidant action impeding or decreasing the stannous ion oxidation, and (5) alteration of the plasma membrane structure or modifying the transport systems of stannous and pertechnetate ions into cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, investigations in basic research have permitted to understand better some properties related with the medicinal plants (Fonseca et al, 2005;Bernardo-Filho et al, 2005). Sambucus australis, known as sabugueiro in Brazil, is used in folk medicine as diuretic, to treat inflammation, burn, pain and rheumatologic disorders (Guarrera et al, 2005;Jorge et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Red blood cells labeled with technetium-99m (99mTc-RBC) have been used in nuclear medicine in a number of evaluation procedures for the gastrointestinal bleeding sites (Wong et al, 2004;Zaman et al, 2004;Olds et al, 2005), peripheral arterial blood flow (Harel et al, 2005), hepatic hemangiomas (Artiko et al, 2004;Verdu et al, 2005), renal carcinoma (Cortes et al, 2003) and splenic reticuloendothelial system (Jin et al, 2004;Slart et al, 2004). Data have shown that some drugs can modify the labeling of blood constituents, such as the RBC, with 99mTc and should alter the results obtained in the daily routine procedures in nuclear medical laboratories (Hladik III et al, 1987;Capriles et al, 2002;de Oliveira et al, 2002;Frydman et al, 2004;Fonseca et al, 2005). The aim of this work was to investigate the in vitro and in vivo effects of acetylsalicylic acid on the labeling of blood constituents with 99mTc.…”
Section: Introductionmentioning
confidence: 99%